A Socio- Demographic Profile of Infant Deaths in A Tribal Block of South Gujarat - Patel, Amul; Kumar, Pradeep; Godara, Naresh; Desai, Vikas K (National Journal of Community Medicine, 2011)
With progressive reduction in infant mortality rate (IMR) and advent of technology, socio – demographic determinants assume more importance (than biological), more so in remote and inaccessible areas, which incidentally also record high IMR. Study was carried out in a tribal block of South Gujarat to generate socio- demographic profile for 48 infant deaths reported during one year. Data was collected through house to house survey on a designed questionnaire. Amongst 48 death cases, literacy rates amongst mothers and fathers were 64.6 and 75% respectively. Occupation wise 81.3% fathers and 52.1% mothers were farm laborer. Joint families were in 81.3% cases and 85.4% belonged to lower social class. Teenage pregnancy was found in 56.3% cases. Age of 25% mothers’ at birth was below 20 years. First birth order was found in 47.9% cases. Birth spacing was less than 2 years in 60.4% cases. It is concluded that improving literacy, increasing age at pregnancy, increasing birth spacing (> 2 years) along with overall socioeconomic improvement of community can help in attaining the further reduction in infant mortality.